Standar Kecantikan sebagai Modal Simbolik - Difa Dwi Sanjaya; Ghania Salsabilla Nihel Fazila; Nesa Utami; Vieronica Varbi Sununianti; Istiqomah Istiqomah; Deni Aries Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of social media and popular culture has influenced how society interprets Beauty. Beauty standards are no longer purely subjective, but have become a social construction that tends to be homogeneous and shaped by media and capitalist interests. In this context, Beauty is understood not only as an aesthetic attribute, but also as a form of symbolic capital that holds social value and can influence an individual’s position in society. This study aims to analyze how Beauty standards function as symbolic capital and how the processes of construction and internalization occur within social life. The method used is a qualitative approach with a literature review of five scientific journals discussing Beauty, body commodification, and power relations. The findings show that Beauty standards are constructed by media and continuously reproduced in everyday practices. Beauty functions as symbolic capital that provides social advantages through the phenomenon of Beauty privilege. In addition, these standards are internalized within individuals’ habitus and contribute to the reproduction of social inequality in society.